2013
DOI: 10.5267/j.ijiec.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A multi-objective improved teaching-learning based optimization algorithm for unconstrained and constrained optimization problems

Abstract: The present work proposes a multi-objective improved teaching-learning based optimization (MO-ITLBO) algorithm for unconstrained and constrained multi-objective function optimization. The MO-ITLBO algorithm is the improved version of basic teaching-learning based optimization (TLBO) algorithm adapted for multi-objective problems. The basic TLBO algorithm is improved to enhance its exploration and exploitation capacities by introducing the concept of number of teachers, adaptive teaching factor, tutorial traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, statistical approaches such as Taguchi method [15][16][17], Response Surface Methodology [10,18], Grey Relational Analysis (GRA) [14,[19][20][21]; soft computing techniques (ANN & ANFIS [22]) and artificial intelligence such as Genetic Algorithm (GA) [23], Particle Swarm Optimization (PSO) [24,25], and Teachinglearning-based optimization (TLBO) [26] techniques have been used to optimize the process parameters which influence tribological and machining behaviour of composites. However, it is observed that most of the results are not favourable due to the uncertainty associated with the process variables.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, statistical approaches such as Taguchi method [15][16][17], Response Surface Methodology [10,18], Grey Relational Analysis (GRA) [14,[19][20][21]; soft computing techniques (ANN & ANFIS [22]) and artificial intelligence such as Genetic Algorithm (GA) [23], Particle Swarm Optimization (PSO) [24,25], and Teachinglearning-based optimization (TLBO) [26] techniques have been used to optimize the process parameters which influence tribological and machining behaviour of composites. However, it is observed that most of the results are not favourable due to the uncertainty associated with the process variables.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many other cooperative population-based approaches have been proposed, for example, teachinglearning optimization [12], [13], which mimics the learning process of a class. In particular, there is a class of students, whose scores are the quality of the associated solution.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the novel single-objective algorithms have been furnished with appropriate mechanisms to deal with multi-objective problems (MOP) also. Few of them are Non-sorting Genetic Algorithm (Deb et al, 2000), Strength Pareto Evolutionary Algorithm (SPEA-II) (Zitzler et al, 2001), Multi-objective Particle Swarm Optimization (MOPSO) (Coello & Lechuga, 2002), Dragonfly Algorithm (Mirjalili, 2016), Multi-objective Jaya Algorithm (Rao et al, 2017), Multi-objective improved Teaching-Learning based Algorithm (MO-iTLBO) (Rao & Patel, 2014), Multi-objective Bat Algorithm (MOBA) (Yang, 2011), Multi-objective Ant Lion Optimizer (MOALO) , Multi-objective Bee Algorithm (Akbari et al, 2012), Non-dominated sorting MFO (NSMFO) , Multi-objective Grey Wolf Optimizer (MOGWO) (Mirjalili et al, 2016), Multi-objective Sine Cosine Algorithm (MOSCA) , Multi-objective water evaporation algorithm (MOWCA) (Sadollah & Kim, 2015) and so forth.…”
Section: Introductionmentioning
confidence: 99%